The distribution and some biological characters of Bacillus thuringiensisin soil of Cat Ba national park - Thanh Hanh, Nguyen Thi; Minh Thanh, Le Thi; Binh, Ngo Dinh; Hop, Duong Van (Academia Journal of Biology, 2014)
Bacillus thuringiensis is a Gram-positive bacterium that produces one or more insecticidal crystal protein during sporulation. These proteins are toxic to insect larvae in the orders Lepidoptera, Diptera ,Coleoptera…and has been developed as a successful biological agent to control insect pests. The Catba National Park is tropical biographical regions: forest ecosystems (primary forest, secondary forest, mangrove forest…), sea ecosystem, spelaean ecosystem, agricultural ecosystem and contains a rich and unique biodiversity: 745 plant species, 282 animal species, 196 sea fish species… Twenty-four soil samples were collected at the five sites in the Catba National Park. A total of 193 strains of Bacillus cereus group were isolated from these soil samples collected. Of these, 28 were identified to Bacillus thuringiensi (Bt) by producing parasporal inclusions. Occurrence of Bacillus thuringiensis in soil of Catba National Park was abundant. Bt freequency in soil of Catba island is 45.83% and average Bt index its 0.145. Average Bt index in soil of the natural ecosystem (primary forest, secondary forest: 0.14 - 0.29) higher in soil of the agricultural systems (0.02 - 0.06). Serologically, 21 isolates (75%) were identified to 9 H serogroup, 7 isolates (25%) were untestable. Nigh isolates (32.14%) belong to the serovar kurstaki (fig. 1A, 1B, 1C) were predominant serotype in Catba Bacillus thuringiensis collection. Fifteen of 28 strains were tested for toxic activity against diamondback moth larvae (Plutella xylostella), some of them killed diamondback moth larvae at high activity: 81 - 100%: 5 strains (33.33%) at 105 CFU/ml and 7 strains (46.67%) at 107 CFU/ml. Eigh strains with high activity were detected gene cry1 type by multiplex PCR method with specific primes for 8 gen. 7 strains contained various cry1 genes. Cry1Aa gen was detected in all of 7 strains (41.18%), cry1Ac was 29.41%, cry1Ab was 23.53% and cry1C was 5.88%.